Math, asked by anitabanpure, 6 months ago

(x - 1)(x + 6) - (x-2)(x - 3) = 3

who will ans he is pro
I give them 88 points​

Answers

Answered by sasmitaray35
1

x=1.5

Step-by-step explanation:

multiply the above simplification then

implies that 10x-12=3

implies that 10x=3+12=15

x=1.5

hope this helps

please mark me as brainliest

Answered by BTSARMY61
1

 = (x - 1)(x + 6) - (x - 2)(x - 3) = 3

 =  {x}^{2}  + 6x - x - 6 - ( {x}^{2} - 3x - 2x - 6 = 3

 =  {x}^{2}  + 5x - 6 -  {x}^{2}  + 3x - 2x -6  = 3

 = 10x - 12 = 3

 = 10x = 3 + 12

 = 10x = 15

x =  \frac{15}{10}

x =  \frac{3}{2}

Similar questions